An industrial heritage Site – S. Pedro da Cova mining complex 1795-1973 - Veludo, Sérgio (2016)
As Joel Cleto and Suzana Faro (2000) states, the mines of S. Pedro da Cova had its origin with the discovery of the anthracite coal diggings in 1795, changing this place habits until 1970. These mines don’t produce over forty years, but the memories of the working time are still present in that village of the city of Gondomar. In this context, and according to the same authors, two privileged places appeared on the defence of the industrial and mining memories of this global heritage: “Cavalete” and “Casa da Malta” (nowadays transformed into “Museu Mineiro”) (Cleto and Faro, 2000: 20). Due to the rapid degradation of this mining complex and the lack of political and sustainable solutions, which could start by an understanding between institutions, this paper intends to promote an international discussion, in order to find paths to restore and value such important Industrial Heritage Place and considering the case study from the mining complexes of Lumere, Asturias, Spain.